INCREASING STUDENT INTEREST IN ISLAMIC CULTURAL HISTORY THROUGH THE SOCIODRAMA METHOD AT MTSN 2 BUNGO - Nur Fadhillah, Maulidia; Surayya, Ely; Simurni, Simurni; Syefrinando, Boby (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: The low level of student interest in learning Islamic Cultural History at MTsN 2 Rimbo Tengah District, due to monotonous and lecture-dominated teaching methods, is the focus of this study. Purpose: The study aims to increase student interest and engagement in learning through the application of the sociodrama method. Method: Using a two-cycle Classroom Action Research (CAR) design with 30 eighth-grade students as subjects, data were collected through observation, questionnaires, and documentation, then analyzed quantitatively and qualitatively. Result: The results showed an increase in learning interest from 67.78% (strong category) in cycle I to 83.09% (very strong category) in cycle II. Student activity in discussions, role-playing, and problem-solving also increased consistently. Conclusion: This study proves that sociodrama is effective in increasing student interest and engagement in learning, and has the potential to be applied to other subjects that require an interactive and participatory approach.